Comparison of metformin and repaglinide monotherapy in the management of newly diagnosed diabetes mellitus type 2: a prospective study - Rahim, Nouman; Munir, Ahad; Rehman, Qavi Ur; Durrani, Hassan Ali; Wahab, Abdul; Khalid, Ahmed; Muneer, Fahad; Irshad, Sumbal; Khan, Tayyab Mumtaz; Akram, Jehanzeb (International Journal Of Community Medicine And Public Health, 2024)
Background: Diabetes Mellitus Type 2 (DMT2), which is characterized by the raised blood sugar level due to insulin resistance in body cells, has now become global epidemic. This study was aimed to compare the efficacy of metformin and repaglinide monotherapy in patients with newly diagnosed DMT2. Methods: This randomized comparative prospective study was performed in a tertiary care hospital of Lahore. 108 Patients’ enrollment was made via simple random sampling technique and a developed inclusion and exclusion criteria. Patients were divided into metformin and repaglinide groups via lottery method. Self-designed proforma was applied for data collection. Data analysis was done in SPSS version 25.0. Results: There was no significant difference in the means of pretreatment (p=0.08) and posttreatment (p=0.10) fasting blood sugar levels between two groups, while significant differences between the means of pretreatment and posttreatment fasting blood sugar levels within metformin group (p=0.02) and repaglinide group (p=0.01) were noted. Likewise, there was no significant difference in the means of pretreatment (p=0.07) HbA1C levels of two groups; however, significant difference was observed in the means of posttreatment (p=0.04) HbA1C of two groups. Moreover, significant differences were also seen between the means of pretreatment and posttreatment HbA1C levels in both metformin group (p=0.03) and repaglinide group (p=0.01). Conclusions: This study suggests that although both metformin and repaglinide are effective in the new-onset T2DM managementz; however, reduction in fasting blood sugar level and HbA1c was more in repaglinide group.